Easy Japanese phrase book : over 1500 common phrases for everyday use and travel. - Lingo Mastery (Firm) ([United States?] : Lingo Mastery, 2023)
Most textbooks are made to teach you the traditional rules and structures of a language and are great for getting around the grammar and spelling questions you may have. However, how many of them provide you the tools necessary to have a common conversation with a best friend or someone you've just met? Not many at all. Language learners often complain about this - a lack of material that can help you familiarize yourself with the most common phrases used in everyday conversation and in native surroundings.
CSE
Trim Education
Text in English and Japanese.
Keywords: Japanese language -- Conversation and phrase books -- English; Japanese language -- Textbooks for foreign speakers -- English; Japanese language -- Study and teaching; Japanese language -- Self-instruction.; Japanese language -- Writing